Perbedaan Aktivitas Fisik pada Pasien Asma Terkontrol Sebagian dengan Tidak Terkontrol di RSUD Dr. Moewardi - Olivia Dwimaswasti; . Harsini; . Isdaryanto (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background:Asthma can interfere with the fulfillment of the needs and proven to reduce the productivity and quality of life for the sufferer. Although asthma rarely cause death, disease often cause problems in both children and adults. Asthma can cause interference with daily activities and emotional disorders (anxiety, depression). Asthma can be mild and do not interfere with daily activities but also be persistent and interfere with daily activities. This studyaimedto determine differencesof physicalactivity between partlycontrolled andnotcontrolledasthma patient at theRSUDDr. Moewardi. Methods:This analytic study was observational using cross sectional approach. A sample of 60 study subjects was selected by purposive sampling from outpatients who visited Pulmonology Clinics, RSUD Dr. Moewardi Surakarta. The data was collected by interview and some datas taken from the medical records. The data was analyzed using logistic regression model on SPSS 17.00 for windows. Results:Inpartilycontrolledasthmawithlowphysical activity11 people(36.7%), moderate physicalactivity10people(33.3%) andhigh activity9people(30%). While in thenot controlledasthma with low activity24people(80%), moderate activity5 people(16.7%) and thehighactivity 1 person(3.3%).Differencesin physical activityin asthma patientspartlycontrolledand not controlledwithlowphysical activityx2=12.895, p= 0.002; OR=19.6(95% CI2.20up to174.72, p =0.008)and thedifferences inphysical activityin patientspartlycontrolledasthmaand not controlledwithmoderate physicalactivityx2=12.895, p= 0.002; OR=4.5 (CI 95%0.44up to46.17, p =0.205). Conclusions:There are differencesof physicalactivity between partlycontrolled andnotcontrolledasthma patient. Keywords:asthma bronchiale, control asthma, physical activity